Accounting Students’ Perceptions of a Learning Management System: An International Comparison - Basioudis, I.; De Lange, Paul; Suwardy, T.; Wells, P. (Emerald, 2012)
Purpose – The purpose of this study is to investigate student perceptions of the design features included in an “off the shelf” Learning Management System (LMS) in teaching undergraduate accounting students. Design/methodology/approach – Questionnaire responses from 846 accounting students studying in the UK, Australia and New Zealand provide international data to develop a model to explain student perception of the LMS. Findings – The final model shows student satisfaction with the use of a LMS is positively associated with three variables: usefulness of lecture notes, bulletin boards and discussion forums, and other LMS tools. Further, the comparison of cultural differences of the three countries shows all students treat the provision of notes as a desirable attribute on a LMS. Findings also suggest that although students find the provision of materials over the LMS does not enhance student engagement in class, overall a comparison of the three countries shows all students treat the provision of notes as a desirable attribute of a LMS. Research limitations/implications – Future research should collect ethnicity data to enable an analysis of cultural influence on student perceptions of the LMS. Practical implications – As increased motivation to learn is found to contribute to improved achievement of learning outcomes, the study’s findings have implications for faculty contemplating the adoption of a LMS in their courses. The findings specifically confirm that usefulness of lecture notes, use of bulletin/discussion boards, and other LMS tools are positively endorsed by students and hence increase their motivation to learn. Originality/value – The current paper adds to the literature as the motivation to use and engage with LMSs by accounting students is not well understood.